A Study of Teacher Engagement with Junior Cycle: Have You Asked the Teacher? - Mulcahy, Grainne (Trinity College Dublin. School of Education. Discipline of Education, 2022)
he Irish education system has been undergoing significant reform since the introduction of the Framework for Junior Cycle 2015. The programme of reforms was begun in the lower second level serving 12 to 15-year-olds. The reforms entailed a substantial shift in teacher practice and assessment changes intended to improve the learner experience and outcome at this level. This study explores teacher engagement with all aspects of the reforms from the teachers' perspective. World Café style data collection underpinned by the principles of participatory research was used in this qualitative study. There has been little research undertaken into teacher engagement with the reforms. To date, research has focused on policy, systemic reviews, the rationale for change and assessment changes. Few have reflected on teacher perceptions of the reforms. In light of proposed Senior Cycle reform valuable insights could be gained from this study of teacher engagement with in-service and enactment of the changes in curricula and pedagogy. The study provides compelling evidence of a shift in teacher classroom practice at lower second level. It identifies the Leaving Certificate examination at the end of Senior Cycle as a key factor impacting teacher perceptions around the reforms. The study suggests additional research is needed to clarify the new role and function of Junior Cycle and further explore the barriers Irish teachers encountered as they engaged with the reform process.
APPROVED
Keywords: Junior Cycle; Irish educational reform; Teacher professional development; Teacher engagement with reform.; Curricular reform; World Café